Targeting PI3K/AKT signaling for treatment of idiopathic pulmonary fibrosis - Jincheng Wang; Kaili Hu; Xuanyan Cai; Bo Yang; Qiaojun He; Jiajia Wang; Qinjie Weng (Acta Pharmaceutica Sinica B, 2022)
Idiopathic pulmonary fibrosis (IPF) is a chronic progressive fibrotic interstitial pneumonia with unknown causes. The incidence rate increases year by year and the prognosis is poor without cure. Recently, phosphatidylinositol 3-kinase (PI3K)/protein kinase B (PKB/AKT) signaling pathway can be considered as a master regulator for IPF. The contribution of the PI3K/AKT in fibrotic processes is increasingly prominent, with PI3K/AKT inhibitors currently under clinical evaluation in IPF. Therefore, PI3K/AKT represents a critical signaling node during fibrogenesis with potential implications for the development of novel anti-fibrotic strategies. This review epitomizes the progress that is being made in understanding the complex interpretation of the cause of IPF, and demonstrates that PI3K/AKT can directly participate to the greatest extent in the formation of IPF or cooperate with other pathways to promote the development of fibrosis. We further summarize promising PI3K/AKT inhibitors with IPF treatment benefits, including inhibitors in clinical trials and pre-clinical studies and natural products, and discuss how these inhibitors mitigate fibrotic progression to explore possible potential agents, which will help to develop effective treatment strategies for IPF in the near future.